Acute Rheumatic Fever After Group A Streptococcus Pyoderma and Group G Streptococcus Pharyngitis. Issue 7 (July 2017) - O'Sullivan, Lance; Moreland, Nicole J.; Webb, Rachel H.; Upton, Arlo; Wilson, Nigel J.
Abstract : A case of acute rheumatic fever (ARF) in an Indigenous Maori child in New Zealand after Group A Streptococcus pyoderma and Group G Streptococcus pharyngitis is reported. The case demonstrates that ARF can develop in the absence of GAS pharyngitis and highlights a need for further research into the role of pyoderma and non-Group A Streptococci infections in ARF pathogenesis.